2016
DOI: 10.15580/gjemps.2016.5.122116219
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Seasonal Variation in Physico-chemical Quality of Ikoli Creek, Niger Delta, Nigeria

Abstract: This study assessed the Spatial and seasonal variation in Physico-chemical quality of Ikoli creek, Niger Delta, Nigeria. Triplicate samples were obtained from 5 locations for a two seasons viz; March and June, 2014. The water samples were analyzed following standard methods. Mean seasonality results for dry and wet were 27.47 and 27.33 o C (temperature), 6.78 and 7.102 (pH), 27.766 and 42.738 µS/cm (conductivity), 45.492 and 29.354 NTU (turbidity), 7.298 and 23.868 mg/l (total dissolved solid), 24.45 and 10.71… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 4 publications
1
14
0
1
Order By: Relevance
“…Like other region of the Niger Delta, two predominant seasons occurs in the region. The climate characteristics of the area have been widely reported by Ogamba et al (2015a-c), Seiyaboh et al (2016), Agedah et al (2015), Aghoghovwia and Ohimain (2014).…”
Section: Study Areamentioning
confidence: 77%
See 2 more Smart Citations
“…Like other region of the Niger Delta, two predominant seasons occurs in the region. The climate characteristics of the area have been widely reported by Ogamba et al (2015a-c), Seiyaboh et al (2016), Agedah et al (2015), Aghoghovwia and Ohimain (2014).…”
Section: Study Areamentioning
confidence: 77%
“…For instance, Seiyaboh et al (2016) reported lower conductivity, nitrite, nitrate, sulphate, magnesium, sodium, potassium, total nitrogen, carbon: nitrogen ratio; higher total hydrocarbon content; and comparable pH, calcium and phosphate concentration sediment from Ikoli creek. The variation may be due to difference in anthropogenic activities in the creeks and effect on runoff on water quality and its sediment.…”
Section: Wwwgjournalsorg 102mentioning
confidence: 95%
See 1 more Smart Citation
“…The authors also asserted that chemical oxygen demand in contaminated water/effluents/wastes is also higher than the biological oxygen demand probably due to oxidation processes that takes place over a short period of time. Instance of dissolved oxygen exceeding the recommended value of 6mg/l by WHO [67] in several surface water resources in Bayelsa state including Nun river [5,15], Epie creek [71], Tombia bridge construction area of River Nun [32], Efi lake [63], Ikoli creek [72], Sagbama creek [11] and extreme low values have been reported in Nun river estuary [26], Igbedi creek [31]. For Biological oxygen demand, the values variously reported in within the permissible limit of 50mg/l specified by WHO [69].…”
Section: Oxygen Related Parametersmentioning
confidence: 99%
“…For instance, in Bayelsa state several rivers, ponds, lakes and creeks exist including River Nun (Agedah et al, 2015;Ogamba et al, 2015a), Kolo creek (Ogamba et al, 2015b;Seiyaboh et al, 2016a), Ikoli creek (Ogamba et al, 2015c(Ogamba et al, , 2016Seiyaboh et al, 2016b), Sagbama creek (Seiyaboh et al, 2017a,b), Igbedi creek (Seiyaboh et al, 2013a,b), Epie creek (Seiyaboh et al, 2016c), Efi lake (Angaye and Meiyepa, 2015), Lake Adigbe among others. (Ohimain and Akinnibosun, 2010, 2008Agedah et al, 2015;Ogamba et al, 2015a-c;Seiyaboh et al, 2016b). Basically, Water hyacinth (Eichhornia crassipes) is an invasive and noxious freshwater weed causing serious threats to water ecosystems (Nyananyo et al, 2007;Ogamba et al, 2015a-d;Ulaeto et al, 2012;Baral et al, 2011;Shanab and Shalaby, 2012).…”
Section: Wwwgjournalsorgmentioning
confidence: 99%